2019
DOI: 10.26803/ijlter.18.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as Psychologist: Experience in Beginner Level of Creative Writing Classes Using Behavior Modification

Abstract: This article is a part of an investigative research report on students' behavior towards creative writing using a psychological approach. This research was carried out for one semester (4 months). This study aims to explore experiences in beginner level creative writing classes. As we all know, there have been many studies on creative writing, but only a few which discussed creative writing using psychological approaches. This research focused on problems in learning to write creatively and behavior modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Creative writing through indigenous psychology eases students in writing and it provides more benefits for the writers. As is in line with the studies conducted by Ahmadi (2019bAhmadi ( , 2020a, it showed that research in learning writing is more optimal through a psychological approach because the study of psychology in learning writing focuses more on the students as the "main character" in learning. By recognizing the psychological context of the students will be easier to provide the learning material.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Creative writing through indigenous psychology eases students in writing and it provides more benefits for the writers. As is in line with the studies conducted by Ahmadi (2019bAhmadi ( , 2020a, it showed that research in learning writing is more optimal through a psychological approach because the study of psychology in learning writing focuses more on the students as the "main character" in learning. By recognizing the psychological context of the students will be easier to provide the learning material.…”
Section: Discussionsupporting
confidence: 83%
“…Adapting Creswell's (2017) view, qualitative-narrative puts forward narration in the presentation of data. The narration is based on the researcher's interpretation of the analyzed text (Ahmadi, 2019b(Ahmadi, , 2020b(Ahmadi, , 2021a(Ahmadi, , 2021b. Therefore, the presentation of data is more non-statistical.…”
Section: Methodsmentioning
confidence: 99%
“…The study of criminal psychology in literature is based on the fact that psychology can be included in the literature (Ahmadi, 2015(Ahmadi, , 2019a(Ahmadi, , 2019b2020a;Ahmadi, Ghazali, Maryaeni, & Taufik, 2019;Ahmadi, 2020b;Hammond, 2014;Wellek & Warren, 2019). The inclusion of criminal psychology in the literature is associated with the behavior of the figures contained in the literature that indicate a crime.…”
Section: Introductionmentioning
confidence: 99%
“…First, teachers are not only motivators, role models, psychologists (Ahmadi, 2019a;, counselors, learners (Conway & Bulgren, 2016), leaders (Urbanski & Nickolaou, 1997), mediators, but become ethnologists who 'voice out' identity, society situations, or social context. Through teachers as ethnographers, the community can understand the 'voice' that emerges from a teacher that is empirical, reflective, and interpretative.…”
Section: Introductionmentioning
confidence: 99%